2017
DOI: 10.1063/1.4995505
|View full text |Cite
|
Sign up to set email alerts
|

BroadBand spoof surface plasmon polaritons coupler based on dispersion engineering of metamaterials

Abstract: The dispersion curves of spoof surface plasmon polaritons (SSPPs) are typically asymptotically nonlinear, with only one single intersection point with the dispersion curves of couplers. This means that wave-vector matching can be achieved only at a single frequency, leading to a narrow bandwidth of SSPP couplers. In this letter, we propose to achieve broadband SSPP couplers through dispersion engineering of metamaterials. To this end, we investigated the dispersion properties of a metallic patch array (MPA) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Such a surface wave mimics the surface plasmon polariton (SPP) commonly used in plasmonics, and then it is called spoof surface plasmon polariton (SSPP). [ 1 ] Different structured surfaces were proposed for guiding SSPP as conducting surfaces perforated by holes, [ 2 ] mushroom structures, [ 3,4 ] metasurfaces made of square or rectangular patches, [ 5,6 ] and periodic chains of laterally opened, [ 7,8 ] or closed [ 9 ] metallic cuboids (“dominos”). The mushroom‐ and patch‐based structures are commonly considered as an effective impedance surface supporting transverse magnetic (TM) and transverse electric (TE) modes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a surface wave mimics the surface plasmon polariton (SPP) commonly used in plasmonics, and then it is called spoof surface plasmon polariton (SSPP). [ 1 ] Different structured surfaces were proposed for guiding SSPP as conducting surfaces perforated by holes, [ 2 ] mushroom structures, [ 3,4 ] metasurfaces made of square or rectangular patches, [ 5,6 ] and periodic chains of laterally opened, [ 7,8 ] or closed [ 9 ] metallic cuboids (“dominos”). The mushroom‐ and patch‐based structures are commonly considered as an effective impedance surface supporting transverse magnetic (TM) and transverse electric (TE) modes.…”
Section: Introductionmentioning
confidence: 99%
“…The mushroom-and patch-based structures are commonly considered as an effective impedance surface supporting transverse magnetic (TM) and transverse electric (TE) modes. [3][4][5][6]10] A bound TM mode can also be supported by a periodic chain of cuboids. It was experimentally shown that the dispersion curve is invariant with the lateral width of the cuboids [7] and that the dispersion curve moves slightly downward by reducing the lateral size of a metallic grating structure down to subwavelength scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the concepts that effectively mimics SPPs are spoof or designer surface plasmon polaritons 6 , 7 , which have been widely used in different microwave circuits including transmission lines 8 – 16 , filters 17 – 26 , antennas 27 , couplers 28 , splitters 29 , absorbers 30 , and circulators 31 . Unlike genuine SPPs, spoof SPPs are supported by specifically designed structures, predominantly by grooved strips whose geometrical properties are used to tailor the behaviour of spoof SPPs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Heretofore, diverse couplers, the precondition of SSPPs' excitation, have been designed to generate the desired phase gradient along the propagating directions. [15,[25][26][27][28][29] Then, the dispersion of the propagating metasurfaces (PMs) is meticulously designed to couple with the coupler's, transforming incident EM waves into the surface waves. There are two common types of couplers-transmission structure and reflection structure, both of them have been proposed to realize high-efficient performance in SSPPs.…”
mentioning
confidence: 99%